Thanks for sharing [videorecording (DVD)]. - Blumberg, Stuart; Paltrow, Gwyneth, 1972-; Ruffalo, Mark; Robbins, Tim, 1958-; Richardson, Joely; P!nk, 1979-
An unconventional romantic comedy that follows the topsy-turvy lives and loves of three obsessive characters: an overachieving environmental consultant, a stubborn small-business owner and a wisecracking ER doctor. They meet in a support group, and set into motion a life-changing journey filled with laughter and surprises.